Predictors of intention to receive cervical cancer screening among commercial sex workers in Gondar city, northwest Ethiopia: application of the theory of planned behavior - Habitu Birhan Eshetu; Kegnie Shitu; Simegnew Handebo (BMC, 2022)
Abstract Background Cervical cancer is a global public health problem & is the fourth leading cause of cancer morbidity and mortality. Abnormal cervical lesion is common in commercial sex workers and is at a higher risk of developing cervical cancer due to multiple sexual partners besides other factors. Intention is an important predictor of behavior and is an initiative to transform their desire into action. Therefore, this study aimed to assess the predictors of intention to receive cervical cancer screening among commercial sex workers in Gondar city, northwest Ethiopia. Methods A community-based cross-sectional study was conducted from March 27 to May 25, 2021, in Gondar city, northwest Ethiopia. A total of 425 commercial sex workers selected using convenience sampling techniques were included in the study. Linear regression with robust standard errors was carried out to identify predictors of intention to receive cervical cancer screening. A 95% confidence interval and a p-value of less than 0.05 were used to declare statistical significance. Results A total of 393 commercial sex workers participated in the study with a response rate of 92.4%. The mean age of the participants was 27.68 ± 6.62. The median (interquartile range) of intention was 4 (3-4.25). The theory of planned behaviour variables explained 38.51% of the variance in intention to receive cervical cancer screening. Direct subjective norm (β = 0.09), 95% CI (0.05, 0.13)), direct Attitude (β = 0.09, 95% CI (0.04, 0.13)), past behaviour (β = 0.27; 95% CI (0.09, 0.46), and positive HIV status (β = 0.26; 95% CI (0.06, 0.46) were significant predictors of intention. Conclusions Commercial sex workers' intention to undergo cervical cancer screening was high. The theory of planned behavior showed adequate utility in predicting commercial sex workers' intention to receive cervical cancer screening. Participant's attitudes, subjective norm, past behavior, and positive HIV status were important factors affecting their intention to receive cervical cancer screening. Thus, interventions aimed at enhancing commercial sex workers' cervical cancer screening behavior should target creating positive social pressure and attitudinal change towards cervical cancer screening.